Compositions and Lipid-lowering Effects of Water Extract and Theabrownin from Ripe Pu-erh Tea Prepared by Controlled Fermentation - SHAN Bo, GONG Jiashun, WANG Qiuping, GAO Linrui, JIA Man, CHEN Dandan, DING Zhengjiao (Shipin Kexue, 2023)
The compositions of water extract (WE) and crude theabrownin (TB) extract from ripe Pu-erh tea prepared by controlled fermentation were analyzed by Curie point pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS) and high performance liquid chromatography (HPLC) and their regulatory effects on obesity in rats were investigated. SD rats were divided into four groups, namely normal diet, high-fat diet, WE and TB. After gavage for 16 weeks, growth indexes, and serum biochemical indexes, oxidative stress and inflammation indexes were analyzed, and histopathological examination of liver tissues was performed by hematoxylin-eosin (HE) and oil red O staining. Results showed that theabrownin, protein and polysaccharide accounted for a large proportion in WE and crude TB. There were significant differences in the contents of catechin and its derivatives such as gallic acid (GA), epicatechin (EC) and epicatechin gallate (EGCG) between WE and crude TB extract (P < 0.05). The contents of the alkaloids caffeine and theobromine in WE were significantly higher than those in TB (P < 0.05). Seven and 12 compounds were shared by the Curie-point pyrolysis products of WE and TB at 380 and 600 ℃, respectively. In the four samples, the number of phenolic compounds was largest, and caffeine was the most abundant compound. Compared with the high-fat model group, the body mass and Lee’s index of the rats from the WE and TB groups significantly decreased (P < 0.05), and so did the levels of serum triglyceride (TG), serum fasting blood glucose (FBG), liver triglyceride and cholesterol (TC) ( P < 0.05), Moreover, fat accumulation was reduced, the levels of serum superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), nuclear factor E2 related factor 2 (Nrf2), interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) were lowered significantly (P < 0.05). These findings indicate increased antioxidant activity and decreased inflammatory factor levels. Furthermore, histological observations of liver sections showed reduction in steatosis, the number of adipocytes and lipid droplet aggregation. To sum up, the compositions of WE and TB were significantly different; however, both showed a positive effect on mass loss and blood lipid reduction. This study can provide a theoretical basis for the deep processing of tea resources and the development of functional products.